179k views
22 votes
Drag the tiles to the boxes to form correct pairs. Not all tiles will be used.

Match the equivalent expressions.
3x + 3y + 2(2x − y)
11x + y
11x − y
4(x + y) − 3(x + y)
7x + y
x − 4x + 6y + (14x − 5y)
(5x − 3y) − x + 3x − 5y
5(x + y) + 6(x − y)
7x − 8y

Drag the tiles to the boxes to form correct pairs. Not all tiles will be used. Match-example-1
User Chastity
by
5.3k points

1 Answer

14 votes

Answer:

x − 4x + 6y + (14x − 5y) ⇔ 11x+y

(5x − 3y) − x + 3x − 5y ⇔ 7x-8y

5(x + y) + 6(x − y) ⇔ 11x-y

3x + 3y + 2(2x − y) ⇔ 7x+y

Explanation:

Solve the following;

3x + 3y + 2(2x − y)

4(x + y) − 3(x + y)

x − 4x + 6y + (14x − 5y)

(5x − 3y) − x + 3x − 5y

5(x + y) + 6(x − y)

Solve:

3x + 3y + 2(2x − y)


=3x+3y+4x-2y


\mathrm{Group\:like\:terms}


=3x+4x+3y-2y


\mathrm{Add\:similar\:elements:}\:3x+4x=7x


=7x+3y-2y


\mathrm{Add\:similar\:elements:}\:3y-2y=y


=7x+y

Hence, this tiles will be used.

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

4(x + y) − 3(x + y)


\mathrm{Add\:similar\:elements:}\:4\left(x+y\right)-3\left(x+y\right)=\left(x+y\right)


=x+y

Thus, this tiles will not be used.

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

x − 4x + 6y + (14x − 5y)


\mathrm{Apply\:rule}:\quad \:a+\left(b+c\right)=a+b+c


6y+\left(14x-5y\right)=6y+14x-5y


=x-4x+6y+14x-5y


\mathrm{Group\:like\:terms}


=x-4x+14x+6y-5y


\mathrm{Add\:similar\:elements:}\:x-4x+14x=11x


=11x+6y-5y


\mathrm{Add\:similar\:elements:}\:6y-5y=y


=11x+y

Thus, this tiles will be used

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

(5x − 3y) − x + 3x − 5y


\mathrm{Apply\:rule}:\quad \left(a\right)=a


\left(5x-3y\right)=5x-3y


=5x-3y-x+3x-5y


\mathrm{Group\:like\:terms}


=5x-x+3x-3y-5y


\mathrm{Add\:similar\:elements:}\:5x-x+3x=7x


=7x-3y-5y


\mathrm{Add\:similar\:elements:}\:-3y-5y=-8y


=7x-8y

Hence, this tiles will be used

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

5(x + y) + 6(x − y)


=5x+5y+6\left(x-y\right)


=5x+5y+6x-6y


\mathrm{Group\:like\:terms}


=5x+6x+5y-6y


\mathrm{Add\:similar\:elements:}\:5x+6x=11x


=11x+5y-6y


\mathrm{Add\:similar\:elements:}\:5y-6y=-y


=11x-y

Hence, this tiles will be used

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

~Learn with lenvy~

User Mike Christiansen
by
5.4k points